Kontribusi Strategi Pembelajaran Inquiry Dan Pola Komunikasi Dalam Kelas Terhadap Minat Belajar Siswa Di Smp Islam Kedung Kabupaten Jepara - Lukman Hakim, Faiq, Dr. Djalal Fuadi, M.M (2017)
The purpose of this study was to determine: 1) Contribution of inquiry learning strategies to junior high student interest in Islam Kedung Jepara regency. 2) Contribution of communication patterns in the classroom to student interest in SMP Islam Kedung Jepara regency. 3) Contribution of inquiry learning strategies and influence patterns of communication in the classroom to student interest in SMP Islam Kedung Jepara regency. This research includes associative quantitative research. The population in this study were VIII class consist of 150 students in SMP Islam Kedung, Jepara regency. samples are taken as 105 students with proportional random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 13.635 + 0.252 X1 + 0.563 X2. The equation shows that student interest is influenced by inquiry learning strategies and patterns of communication in the classroom. The conclusions drawn are: 1) Contribution the learning strategy inquiry against junior high student interest in Islam Kedung Jepara regency acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 2.737> 2.000 and the significance value <0.05, namely 0.007 with the relative contribution of 18.5% and the effective contribution of 8.4%. 2) Contribution the pattern of communication in the classroom to student interest in SMP Islam Kedung Jepara regency acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 7.449 > 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 81.5% and 37.1% effective contribution. 3) The inquiry learning strategy and influence patterns of communication in the classroom to student interest in SMP Islam Kedung Jepara regency in conducting to contribution can be accepted. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, are 42.611> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.455 indicates that the influence of inquiry learning strategies and influence patterns of communication in the classroom to student interest in SMP Islam Kedung Jepara district is 45.5%, while the rest influenced by other variables.